Pengaruh Integrated Reporting Terhadap Firm Value Di 5 Negara Asean - Devina Gunawan; Toto Rusmanto (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine the effect of integrated reporting disclosure on firm value in 5 Asean countries. This research is a quantitative research using secondary data in the form of integrated reporting. This study uses 1 independent variable, namely integrated reporting which is measured using a dummy variable, 1 dependent variable, namely firm value which is measured using Tobins'q and 4 control variables, namely return on assets, return on equity, firm size, and debt to total asset ratio. . The sample used is 30 companies in 5 Asean countries. The results of this study indicate that integrated reporting has a positive effect on firm value, and control variables that affect firm value, namely return on equity and firm size, in addition to 2 other control variables, namely return on assets and debt to total asset ratio have no effect on firm value. The results of this study indicate that the disclosure of integrated reporting increases firm value in 5 Asean countries. Keywords : Integrated Reporting, Firm Value, ASEAN